2011
DOI: 10.1264/jsme2.me10203
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Genetic Characterization of Aurantimonas and Methylobacterium Strains from Stems of Hypernodulated Soybeans

Abstract: The aims of this study were to isolate Aurantimonas and Methylobacterium strains that responded to soybean nodulation phenotypes and nitrogen fertilization rates in a previous culture-independent analysis (Ikeda et al. ISME J. 4:315-326, 2010). Two strategies were adopted for isolation from enriched bacterial cells prepared from stems of field-grown, hypernodulated soybeans: PCR-assisted isolation for Aurantimonas and selective cultivation for Methylobacterium. Thirteen of 768 isolates cultivated on Nutrient A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
(78 reference statements)
0
19
0
Order By: Relevance
“…Aurantimonas has been found in above-ground parts of plants such as rice, soybean, Arabidopsis thaliana , and Jatropha curcas (1, 5, 16, 18). Their population was likely controlled in a manner similar to that of legume-rhizobia symbiosis (10).…”
mentioning
confidence: 99%
“…Aurantimonas has been found in above-ground parts of plants such as rice, soybean, Arabidopsis thaliana , and Jatropha curcas (1, 5, 16, 18). Their population was likely controlled in a manner similar to that of legume-rhizobia symbiosis (10).…”
mentioning
confidence: 99%
“…To characterize this bacterial group from a genomic viewpoint, we determined the complete genome sequence of Aureimonas sp. AU20, an isolate from the stem of a soybean plant (11). The result showed that the AU20 genome (5.2 Mb in total) contains nine circular replicons: the main chromosome (3.7 Mb) and eight other replicons (designated pAU20a to pAU20g and pAU20rrn) ( Table 1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the strains (A. ureilytica and Aureimonas spp. AU40, D3, and N4) (11,18,19) were similar to AU20 in that their rrn sequences were assembled into small (9.4-10 kb) circular replicons that contained pPS10 repA-like genes and oriV regions similar to pAU20rrn (Fig. 1B and Fig.…”
Section: A Lt a M Ir E N S Is A Fr Ig Id A Q U A E A C O Ra Li C mentioning
confidence: 94%
See 2 more Smart Citations